2008
DOI: 10.3324/haematol.12413
|View full text |Cite
|
Sign up to set email alerts
|

Italian Society of Hematology practice guidelines for the management of iron overload in thalassemia major and related disorders

Abstract: New measures of iron accumulation in liver and heart (superconducting quantum inference device and magnetic resonance imaging), and oral iron chelators (deferiprone and deferasirox) are available for managing iron overload in thalassemia major. To assure appropriate use of these new health technologies, the Italian Society of Hematology appointed a panel of experts to produce clinical practiceguidelines for the management of iron overload in thalassemia major and related disorders. The analytical hierarchy pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
156
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(165 citation statements)
references
References 57 publications
4
156
0
2
Order By: Relevance
“…Furthermore our findings that SF values were more likely to decrease in those patients who began with the highest SF values and lower iron intake from lower transfusion rate (<0.25 mg/kg/day in our study) are consistent with previous individual studies [42][43][44] and review of trends from several studies [38]. Also in the view of without a strong evidence to suggest that deferiprone has superior efficacy than desferoxamine, together with its associated adverse effects, some can be fatal, deferiprone remains the second line therapy for thalassemia major patients whose desferoxamine is inadequate or contraindicated as reviewed [45,46] and documented in all clinical practice guidelines around the world [47][48][49] including the latest registration filed by the US-FDA [50]. In this regard, our study has further confirmed that efficacy of deferiprone monotherapy is rather limited and should not be used as a first-line treatment in patients with transfusion-dependent thalassemia including severe Hb E/b thalassemia.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore our findings that SF values were more likely to decrease in those patients who began with the highest SF values and lower iron intake from lower transfusion rate (<0.25 mg/kg/day in our study) are consistent with previous individual studies [42][43][44] and review of trends from several studies [38]. Also in the view of without a strong evidence to suggest that deferiprone has superior efficacy than desferoxamine, together with its associated adverse effects, some can be fatal, deferiprone remains the second line therapy for thalassemia major patients whose desferoxamine is inadequate or contraindicated as reviewed [45,46] and documented in all clinical practice guidelines around the world [47][48][49] including the latest registration filed by the US-FDA [50]. In this regard, our study has further confirmed that efficacy of deferiprone monotherapy is rather limited and should not be used as a first-line treatment in patients with transfusion-dependent thalassemia including severe Hb E/b thalassemia.…”
Section: Discussionsupporting
confidence: 91%
“…However, any validation study of a diagnostic quantitative procedure must report a determination coefficient (R 2 ) with a prediction interval. Above all, in this specific case, the 95% prediction interval would be reasonably narrow not extending over the identified threshold for iron concentration tissue damage and death [1,12]. However, regression analysis of the entire samples confirms the incomplete adequacy of small samples (i.e., <1 mg dw).…”
Section: Discussionmentioning
confidence: 79%
“…Determination of liver iron concentration (LIC) is essential to predict iron related tissue damage and disease and to guide chelation therapy [1]. Nowadays, only two validated noninvasive methods are available (MRI-R2 and R2*) [2] and liver biopsy continues to be the gold standard for hepatic iron determination.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, albumin, which is a negative acute phase reactant, was included in the analysis [28,29] and there was no statistical significance between ferritin groups. However, serum ferritin level remains the most cost-effective, inexpensive and noninvasive measure for iron overload available worldwide [30,31]. It is important to estimate the significance of iron overload in patients who underwent alloHSCT using non-invasive imaging like liverspecific MRI.…”
Section: Discussionmentioning
confidence: 99%